Effects of gamma radiation on biological development of Aedes Albopictus / Mohd Zulfadli Adenan, Nursyamimi Md Nizam, Nazri Che Dom - Adenan, Mohd Zulfadli; Md Nizam, Nursyamimi; Che Dom, Nazri (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
Dengue is a mosquito-borne viral disease, that may spread across countries. There are two main causes of dengue transmission which are Aedes aegypti and Aedes albopictus. However, in Malaysia, Aedes albopictus overlap the distribution of Aedes aegypti and its population in the certain area showed more dominant than Aedes aegypti. The objective of this study was to investigate the effects of gamma radiation on the biological development, including the hatchability rate, development period, embryonation period and adult emergence of Aedes albopictus. Average total of 360 Aedes albopictus eggs were irradiated with gamma radiation of 5, 10, 15, 20 and 25 Gy. Based on the result, hatchability rate decreased significantly with increasing of gamma radiation doses (p= 0.011). The shortest embryonation period was at day 12; eggs that irradiated with the least gamma dose (5 Gy). For adult emergence, only eggs that irradiated with 5 Gy able to emerge into adult.